Climate Change Impacts Assessment on Logar Water Resources: Challenges and Opportunities - Shirzad, Mohammad Dawod; Sahak, Kawoon (Journal of Natural Sciences – Kabul University, 2024)
In this article, a brief overview of the surface water of Logar province and the effects of climate change on it are evaluated. Several years of information related to air temperature, rainfall, and water flow have been collected and subjected to comprehensive research, and the effects of climate change on these parameters have been evaluated. At the end of the article, the problems and damages caused to Logar's surface water due to climate change have been evaluated and appropriate solutions have been suggested. In the research area, most of which is related to Pul-e- Alam and a small part is related to Barki Barak district, which previously irrigated by five canals: Karamtian, Dastgir, Haroon, Bakhshabad and Nat, also focused on calculation of groundwater extraction. This research is qualitative and quantitative research and primary and secondary data are used. For the preparation of primary data, survey, observation, and interview methods were used and for the preparation of secondary data, books, international articles, authoritative global reports and international sites were used. GIS is used for mapping and Excel programs are used to analyze statistics and figures. Recently, after analyzing data, it was found that a 4-inch well extracts 1.8 liters of water per second, and a 5-inch well extracts 2.8 liters of water per second. After researching, it was found that 471829.05 cubic meters of water extracted to irrigate 5,610 acres of land for one crop season every year through 4 and 5-inch wells in this area of Logar province. It should be noted that the lack of sufficient and reliable data and the lack of cooperation of the local people to collect data were among the major problems in conducting this research. At the end of the article, the problems and damages caused to Logar water resources due to climate change have been evaluated and suggestions have been made to use appropriate management opportunities to realize the green revolution.